Effects of protocatechuic acid on myocardial oxygen consumption and tolerance to anoxia in animals - Rao Man-ren; Liang Man-da (Acta Pharmacologica Sinica, 2016)
Effects of protocatechuic acid(3,4-dihydroxy benzoic acid) were studied in open-chest cats. The blood outflow from the coronary sinus was collected with a plastic cannula inserted into the sinus via the right auricle. Myocardial O2 consumption was calculated as the product of the coronary venous flow multiplied by the arterio-venous O2 difference. It was found that iv protocatechuic acid 50 mg/kg produced a significant reduction in myocardial O2 consumption to about 47% of its initial level. Adrenaline and protocatechualdehyde induced increase in myocardial O2 consumption could be partially antagonized by protocatechuic acid 50 mg/kg. Regional vascular resistances in left coronary circumflex branch of dogs and femormal artery of cats were decreased. In order to test the effects of protocatechuic acid on the tolerance to anoxia of the heart, we established a heart-lung preparation of rat under cryo-anesthesia. This method allows us to measure the time interval during which the heart uses up a certain amount of O2 by performing a constant work load. This duration indicating the “tolerance to anoxia” was defined as the interval between the stoppage of the respiratory pump and the emergence of anoxic failure(cardial output was reduced almost to zero and aortic blood pressure declined sharply). In 57 preparations carbochromene 4 mg and protocatechuic acid 10 mg significantly increased the “tolerance to anoxia” over the controls by about 100% and 60%,respectively.At the end of the anoxic experiment protocatechuic acid and carbochromene alleviated the decline of blood pressure and reduced heart rate more than controls. The determination of the tolerance to anoxia in the heart-lung preparation of rat is recommended as a relatively specific method for the study of effects on the O2 consumption of the myocardium, useful for evaluation of antianginal drugs.